Transformation of Student Science Achievement Through Project-Based Learning (PjBL): A Meta Analysis Study - Safitri, Islamiani (Scientiae Educatia: Jurnal Pendidikan Sains, 2024)
This study aims to evaluate the effectiveness of Project-Based Learning (PjBL) in enhancing students' science achievements through meta-analysis study. By selecting documents in Scopus, ScienceDirect, and Sinta Database using the PRISMA method, 20 documents were obtained and covering 29 studies from 2016 to 2024 which were analyzed using a random-effects model by R-Studio Program. The study results indicate that PjBL has a significantly positive impact on students' science achievements, with an average effect size of 1.12. Variability analysis revealed that the effectiveness of PjBL varies based on the education level, the type of skills developed, geographical location, and sample size. The highest effectiveness of PjBL was found at the elementary and high school levels, with a greater impact on the development of soft skills than cognitive skills in science achievement. The impact of PjBL was also more significant in Africa compared to Asia and Europe. This study underscores the importance of integrating PjBL into the educational curriculum to enhance student achievement in science learning, especially in diverse contexts. These findings provide a strong foundation for educators, policymakers, and researchers to develop and implement effective PjBL strategies.